The Effectiveness of Educational Program based on Explanation of Judgments and the Embodiment of Ideas in Acquisition of Jurisprudential Concepts and Developing Logical Thinking Skills among Secondary Stage Male Students in the State of Kuwait - Al- Shammary, Frahan Ibrahim; Al- Maqosi, Yaseen Ali (Arab Journal for Sciences and Research Publishing, 2020)
The current study aimed to demonstrate the effectiveness of an educational program based on the explanation of judgments and the embodiment of ideas in acquiring jurisprudential concepts and developing logical thinking skills among secondary school students in the State of Kuwait. The study adopted the experimental method. and consisted of (50) eleventh graders from the scientific stream at Sabah Al- Salem Secondary School for Boys, during the first semester of the 2019/2020 academic year. Two sections of the school were intentionally chosen and were randomly distributed into two groups: an experimental group and a control group. To achieve the objectives of the study, the two researchers prepared a test that measures the acquisition of jurisprudential concepts and a scale measuring logical thinking skills. The validity and reliability of the two tools were verified. The results showed that the experimental group exceeded in the acquisition of jurisprudential concepts and in developing logical thinking skills. In view of the study’s result, the study recommended the necessity of holding training courses and workshops for Islamic education teachers to employ the strategy of reasoning of judgments and embodying ideas in teaching Islamic education.